The impact of an interaction-based classroom program on executive function development in low-SES preschoolers: first support for effectiveness - Kellens, Silke; Dieusaert, Fren; De Wilde, Johan; Spilt, Jantine L.; Baeyens, Dieter (Frontiers in Education, 2023)
Studies have shown that children from a low socioeconomic status (SES) family are likely to have lower academic scores, indicating an SES-achievement gap. This inequality already starts in preschool and persists throughout children's lives. Since executive functions (EFs) have been put forward as contributing factors in this SES-achievement gap, it is crucial to target early EF development to remediate the adverse effects of poverty. In this quasi-experimental study, a classroom program delivered by teachers (i.e., "Put your EF glasses on") was implemented to strengthen preschoolers' EFs, consistent with the idea that well-developed EFs can foster school readiness and prevent school failure. The program aimed to boost children's EFs through high-quality teacher-child interactions, EF-supporting activities (e.g., games), and a supportive classroom structure. Teachers (n = 24) and children (n = 224, Mage = 52.61 months) from 8 Belgian schools participated in this quasi-experimental pilot study and were divided into experimental and control groups. Teachers in the experimental group carried out the program (receiving materials and coaching to support implementation), whereas teachers in the control group practiced teaching as usual. Before and after the program, all teachers filled out the BRIEF-P, a questionnaire about daily executive problems in preschool children. We compared the effect of the classroom program in low-SES versus middle-to-high-SES children on EF problem scores. Results revealed that all low-SES children started with significantly higher EF problems (total problem score, working memory, inhibition, and planning and organizing) scores than middle-to-high-SES children. A positive effect of the program was found among low-SES children. More specifically, EF problems (total problem score, working memory, shifting, and planning and organizing) remained stable over time in the low-SES group in the experimental group, but there was no program effect on emotional control and inhibition. In the control group, these EF problems increased for low-SES children, expanding the gap between low and middle-to-high-SES children. There were no program effects for middle-to-high-SES children. These results show that a teacher-mediated classroom program can support EF development, especially in preschoolers at sociodemographic risk.